Specificity of Cryptococcus neoformans factor sera determined by enzyme-linked immunosorbent assay and dot enzyme assay. - Belay, T (1993)
An indirect enzyme-linked immunosorbent assay (ELISA) and a dot enzyme assay (DEA) were used to determine the specificities of Cryptococcus neoformans factor sera to serotype type-specific capsular polysaccharides, glucuronoxylomannans (GXMs). Pure and chemically characterized GXMs were obtained from representative isolates of C. neoformans serotypes A, B, C, and D. Distinctive specificity patterns and quantitative differences were observed for each factor serum when the selected GXMs were studied by ELISA. The specificity patterns for each factor serum determined by DEA almost completely paralleled the ELISA results. The serotype specificities demonstrated by ELISA and DEA were similar to previously reported results that were obtained by slide agglutination studies of whole cells. On the basis of the ELISA and DEA activity patterns, factor sera 5, 6, and 8 were specific for serotypes B, C, and D, respectively; factor serum 1 was strongly reactive to all serotypes; factor serum 2 was specific for serotypes A, B, and D; factor serum 3 was specific for serotypes A and D; and factor serum 4 was specific for serotypes B and C. The specificity of factor serum 7 for serotype A was demonstrated by DEA only. Structural variation was indicated among the serotype C isolates studied because a unique activity pattern versus factor serum 6 was observed for each isolate. The quantitative differences in the activity of the GXMs from five serotype C isolates suggest that mannopyranoside residues substituted O-2 and O-4 with xylose are essential elements of the determinant responsible for the observed activity of factor 6. No significant differences in activity patterns and specificities of factor serum 6 were observed when O-deacetylated GXMs were substituted for the native GXMs. Our results show that ELISA and DEA are valuable techniques for the serological analysis of cryptococcal factor sera and GXMs.